2009
DOI: 10.1007/s12663-009-0077-9
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of ranula in two centres in Malaysia

Abstract: Introduction Ranula is a mucous extravasation cyst which occurs as a result of trauma or obstruction of the sublingual or minor salivary gland or the duct itself.Patients and results 14 patients were seen at Universiti Kebangsaan Malaysia Medical Centre, Kuala Lumpur and Hospital Tunku Ampuan Afzan, Kuantan, Malaysia between 2000 to 2006. There were six cases of intra-oral ranula and eight plunging ranula. Twelve patients underwent surgical intervention while two refused surgery. Four patients (33.3%) from tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
8
0
4
Order By: Relevance
“…Marsupialisation is a less invasive method commonly used for the treatment of congenital ranula. It was reported that two cases of congenital ranula were successfully treated with marsupialisation at the age of 9 and 12 months [22]. However, the method is not always effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marsupialisation is a less invasive method commonly used for the treatment of congenital ranula. It was reported that two cases of congenital ranula were successfully treated with marsupialisation at the age of 9 and 12 months [22]. However, the method is not always effective.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that congenital ranula develops independently of systemic diseases or congenital defects. However, very few authors report the general condition of their paediatric patients [22]. This indicates the need for further studies on congenital ranula in the context of general heath.…”
Section: Discussionmentioning
confidence: 99%
“…Correct diagnosis is crucial as the management of ranula is different and mismanagement will definitely end up with recurrence. 2 We present the case of a 10-year-old girl who presented to us with painful right submandibular swelling for 1 month, then diagnosed to have extensive submandibular abscess radiologically; however, intraoperatively the presence of cystic mass extending from right submandibular space to floor of mouth without any purulent content was noted.…”
Section: Introductionmentioning
confidence: 95%
“…The incidence is about 1 to 10% with the prevalence of 0.2 cases per 1,000 persons. 2 Primary etiology of these lesions is due to partial obstruction of a sublingual duct as a consequence of congenital duct agenesis or trauma that will lead to the formation of an epithelial-lined retention cyst. 3 The other etiology that has been described is extravasation of mucus into the surrounding tissues due to traumatic injury to the duct or salivary acini.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, cervical ranulas appear as soft, slowgrowing masses, and they can affect swallowing, speech, chewing, and even breathing (if particularly large) (4). The acute presentation of ranulas is rare (5).…”
Section: Introductionmentioning
confidence: 99%